Ruptured pseudoaneurysm of the pulmonary artery: rare manifestation of a primary pulmonary artery sarcoma - Koch, Achim; Mechtersheimer, Gunhild; Tochtermann, Ursula; Karck, Matthias (Interactive cardiovascular and thoracic surgery, 2010)
A 64-year-old male developed chest pain while gardening. Aortic dissection and coronary artery disease were excluded but chest computed tomography (CT) scan showed an aneurysmic enlargement of the pulmonary artery and a fluttering structure within. He underwent immediate sternotomy for replacement of the pulmonary artery. Histology showed an intimal sarcoma of both branches of the pulmonary artery. The pulmonary artery was replaced by a T-shaped Gore-Tex-prosthesis.